The Influence of Job Stress and Leader-Member Exchange on Job Performance with Employee Engagement as Mediation - Hasyim, Muhamad Khavid; Sudarma, Ketut (Universitas Negeri Semarang, 2018)
The purpose of this study was to examine the effect of job stress and leader-member exchange on job performance with employee engagement as a mediating variable. The population of this study were all employees of PTPN IX Kebun Getas Afdeling Assinan Kempul. The samples used were 70 Employees. The sampling technique used saturated sample technique. Data collection method used is the method of observation, interview method, and questionnaire method as measured by Likert scale. Analysis of data using multiple regression analysis and path analysis with SPSS program version 23. The results showed that there is no influence job stress on job performance; There is influence job stress on employee engagement; There is influence of leader-member exchange on job performance and employee engagement; There is influence of employee engagement on job performance. The results of this study also show that employee engagement is able to mediate job stress on performance; And employee engagement able to mediate leader-member exchange on job performance employees of PTPN IX Kebun Getas Afdeling Assinan-Kempul.